Incremental detection rate of prostate cancer by real‐time elastography targeted biopsies in combination with a conventional 10‐core biopsy in 1024 consecutive patients. (14th February 2014) - Salomon, Georg; Drews, Nils; Autier, Philippe; Beckmann, Ann; Heinzer, Hans; Hansen, Jens; Michl, Uwe; Schlomm, Thorsten; Haese, Alex; Steuber, Thomas; Graefen, Markus; Becker, Andreas
<x xml:space="preserve">Abstract</x> Objective To quantify the incremental detection rate (DR) of a targeted biopsy in addition to a randomized 10‐core biopsy. Patients and Methods This retrospective study analysed 1024 patients who consecutively underwent a four‐core real‐time elastography (RTE) targeted biopsies in addition to a randomized 10‐core transrectal ultrasonography (TRUS)‐guided biopsy in a primary or rebiopsy setting. The overall DR, the DR of a 10‐core randomized, RTE targeted biopsy and the incremental DR were calculated. Results Overall, randomized and RTE targeted biopsy DRs (for the combination, the 10‐core and the four‐core RTE biopsy scheme) were 46.2% (n = 473), 39.1% (n = 400) and 29.0% (n = 297), respectively. Four‐core RTE targeted biopsies detected an additional 73 patients not detected by the 10‐core randomized biopsies (increase in the overall DR of 7.1%). This represented a relative increase in DR of 18.3%. The incremental DR was better in rebiopsy patients (24.8%) than in patients having their first biopsy (14.7%). Within all patients diagnosed by RTE targeted biopsy only, 34 patients harboured significant Gleason 4 or 5 prostate cancer (PCa), diagnosed by four‐core RTE biopsy only. Moreover, PCa with a Gleason grade of 4 or 5 was detected by four‐core RTE biopsies in 30 patients, who showed low‐grade PCa ≤ Gleason 3 only in the systematic 10‐core biopsy. Conclusions Real‐time elastography targeted biopsy seems to be an appropriate method for increasing the DR of PCa. Nevertheless, RTE targeted biopsies missed a high proportion of patients with PCa and should therefore be considered as an addition to randomized biopsies.